A preliminary study on the synthesis of poly(vinylbenzyl chloride) with different solvents - Manjusha Elizabeth Mathew,; Ishak Ahmad,; Sabu Thomas,; Mohammad Kassim,; Rusli Daik, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Polyvinyl benzyl chloride (PVBC) was synthesized by free radical polymerization of 4-vinylbenzyl chloride using benzoyl peroxide initiator at 60 ℃. PVBC was synthesised in different solvents such as toluene, xylene, 1,4-dioxane, and tetrahydrofuran. The polymers were structurally characterized by 1H NMR and FTIR spectroscopic techniques. The thermal property of the polymer was investigated by thermogravimetric analysis (TGA) and differential thermogravimetric analysis (DTA). The number average molecular weight, weight average molecular weight and polydispersity index of PVBC synthesised in different solvents were determined and compared by gel permeation chromatography technique.